STRUCTURE–ANTIMICROBIAL PROPERTIES STUDY OF SOME DIBASIC PHENYLCARBAMIC ACID ESTERS - Ivan Malík; Jozef Csöllei; Marián Bukovský (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Due to worldwide phenomenon of microbial resistance to commonly used therapeutic agents, antibiotics and antifungals, dibasic di‑/trimethylphenylcarbamic acid esters 1–3, a non-traditional series of potential antimicrobials, has been in vitro evaluated against chosen Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacterial strains as well as against yeast (C. albicans) by the minimum inhibitory concentration (MIC) assay. Taking into consideration chemical structure of tested derivatives, the incorporation of more than one protonated atom of nitrogen into salt forming fragment positively influenced the activity against E. coli. On the contrary, the presence of one or more methyl groups instead of 3-alkoxy side chain attached to lipophilic aromatic moiety has not found to be favorable structural feature. In entire set of inspected compounds, the most promising results have been found for the compound 3, chemically1-[3-piperidinium-1-yl-2-([(2,4,6-trimethylphenyl)amino]carbonyloxy)propyl]piperidinium dichloride, against E. coli with the MIC=1.56 mg/mL. Key words: Dibasic phenylcarbamic acid esters, Escherichia coli, hydrogen bonding, lipophilicity